Presurgical Thalamus Volume in Postoperative Delirium: A Longitudinal Observational Cohort Study in Older Patients. (16th June 2022) - Fislage, Marinus; Feinkohl, Insa; Pischon, Tobias; Spies, Claudia D.; Borchers, Friedrich; Winterer, Georg; Zacharias, Norman
Abstract : BACKGROUND: Previous studies suggest a role of the thalamus in cognitive function, while others implicate it as a central effect site of anesthetics. Yet, its role in postoperative neurocognition in the aging brain remains uncertain. We used presurgical thalamic volume as a functional indicator and determined its association with postoperative delirium (POD). METHODS: For this study, 301 older adults (aged ≥65) without dementia and scheduled for surgery were enrolled. Before surgery, participants underwent magnetic resonance imaging (MRI). Thalamus volume was segmented using Freesurfer (Version 5.3.). Participants were screened for POD twice a day until discharge or for a maximum of 7 days. POD was defined as a positive screening on ≥1 of 4 validated instruments: Richmond Agitation Sedation Scale (RASS), Nursing Delirium Screening Scale (Nu-DESC), Confusion Assessment Method (CAM), and Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) score. A logistic regression associated thalamus volume with POD with adjustment for age, global brain atrophy, and physical status according to the American Society of Anesthesiologists (ASA) classification. RESULTS: In this cohort, 44 participants (14.6%) were diagnosed with POD. Independently of age, global brain atrophy, and physical status score, a higher preoperative thalamus volume was associated with a reduced odds of POD (odds ratio per 1-cm 3 increment; 0.73 [95% confidence interval (CI), 0.58–0.92]; P = .008). CONCLUSIONS: A larger thalamus volume was associated with reduced odds of POD. Thus, the thalamus marks a region of interest in POD in the aging brain. These findings may help to understand the neuronal basis of POD.